A Narrative Review of the Utilization of Motivational Interviewing for Nutritional Counseling in Dentistry - Anderson, Heather; Rulli, Danielle; Sutton, Julie D; Theis-Mahon, Nicole; Arnett, Michelle C (Journal of dental hygiene, 2025)
The purpose of this narrative review was to explore how motivational interviewing (MI) and brief MI are utilized for nutritional counseling in oral health care to support patient-centered dietary behavior change. This narrative review followed PRISMA format. A search strategy was designed using MeSH terms and keywords with inclusion and exclusion categories dictating the search. Searches were conducted in Ovid Medline ALL, CINAHL, Scopus, and Web of Science. Studies were screened in Rayyan by two independent reviewers. Eligible studies were categorized into two domains: MI utilization by provider type or setting and MI application for a population or a condition. The search yielded 122 articles. After title and abstract screening, 113 articles were excluded. Following full-text review, three more were removed, resulting in six (n=6) studies for inclusion. Four studies examined the utilization of MI by provider type or setting. These studies demonstrated MI training improved provider confidence and interest in delivering nutritional counseling, with brief MI interventions showing effectiveness in dietary behavior change. Two studies focused on the application of MI for a population or condition. Motivational interviewing and brief MI can be utilized for nutritional counseling in oral health care settings by dental hygienists to enhance their confidence, promote patient behavior change, and contribute to improved dietary habits for improved oral and systemic health. The Nutritional Risk Assessment and Counseling Tool (NRACT) can be used as a risk assessment and guide to facilitate brief MI in a dental setting for nutritional counseling.